2016
DOI: 10.1002/ep.12511
|View full text |Cite
|
Sign up to set email alerts
|

Sulfated Ce‐doped TiO2 as visible light driven photocatalyst: Preparation, characterization and promotion effects of Ce doping and sulfation on catalyst performance

Abstract: Sulfated Ce‐doped TiO2 photocatalysts, with improved visible light photocatalytic activity, are prepared by sol‐gel method and via impregnation with diluted sulfuric acid. The synthesized samples are characterized by means of X‐ray diffraction (XRD), transmission electron microscopy (TEM), ultraviolet–visible diffuse reflectance spectra (UV–Vis DRS), Fourier transform infrared (FTIR) spectroscopy, temperature‐programmed desorption of ammonia (NH3‐TPD) and X‐ray photoelectron spectroscopy (XPS). To investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Hence, the excited electrons could easily be trapped by Ce 4+ , present on the material. Due to the Lewis acidic nature of Ce 4+ ions, it seems to be superior to the oxygen molecule (O 2 ) in electron trapping ability. , Afterward, the electrons might be abstracted by the adsorbed O 2 by oxidation process, producing O 2 •– , which facilities the formation of • OH. On the other hand, the holes are trapped by Ce 3+ (i.e. converstion of Ce 4+ ), which helps the formation of • OH and regeneration of Ce 3+ simultaneously.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the excited electrons could easily be trapped by Ce 4+ , present on the material. Due to the Lewis acidic nature of Ce 4+ ions, it seems to be superior to the oxygen molecule (O 2 ) in electron trapping ability. , Afterward, the electrons might be abstracted by the adsorbed O 2 by oxidation process, producing O 2 •– , which facilities the formation of • OH. On the other hand, the holes are trapped by Ce 3+ (i.e. converstion of Ce 4+ ), which helps the formation of • OH and regeneration of Ce 3+ simultaneously.…”
Section: Resultsmentioning
confidence: 99%
“…Because ROS are highly reactive and nonselective, they can oxidize and decompose a variety of harmful compounds into CO 2 and inorganic ions. As shown in Figure 4d, we can see that after the degradation of the organic compound, two peaks at 900.8 eV and 882.5 eV can be assigned to the binding energies of Ce 3d5/2 and Ce 3d3/2 of Ce 4+ [67,68]. Additionally, the other two peaks at 905.1 eV and 886.65 eV are assigned to the binding energies of Ce 3d5/2 and Ce 3d3/2 of Ce 3+ [69,70].…”
Section: Mechanism Studymentioning
confidence: 85%
“…A possible catalytic mechanism was proposed in Figure 5, where the existence of Na3C6H5O7•2H2O enhanced the reduction of CeO2 to form a 20-30 nm sized microspheres. The CeO2 microsphere, having an average diameter of 6.22 nm, was well dis- As shown in Figure 4d, we can see that after the degradation of the organic compound, two peaks at 900.8 eV and 882.5 eV can be assigned to the binding energies of Ce 3d 5/2 and Ce 3d 3/2 of Ce 4+ [67,68]. Additionally, the other two peaks at 905.1 eV and 886.65 eV are assigned to the binding energies of Ce 3d 5/2 and Ce 3d 3/2 of Ce 3+ [69,70].…”
Section: Mechanism Studymentioning
confidence: 89%
“…It has been demonstrated that coupling a-Fe 2 O 3 to other metal oxide semiconductors could overcome these drawbacks [19]. The presence of these hydrated complexes could capture the photo-generated electrons, which significantly contributes to the photocatalytic activity of HC due to the following reasons [24]: (1) the effective separation of the photogenerated electrons and holes; and (2) the mitigation of the recombination of the electron/hole pairs. The efficient charge separation can increase the lifetime of the charge carriers and enhance the efficiency of the interfacial charge transfer to adsorbed substrates and participate in the reduction and oxidation reactions.…”
Section: Discussion Of the Photocatalytic Mechanismmentioning
confidence: 99%
“…Furthermore, hydrated complexes (Al(OH) 1 , Fe(OH) 1 ) can be formed onto the HC surface for supporting significant electrostatic attractions when it immersed in water [23]. The presence of these hydrated complexes could capture the photo-generated electrons, which significantly contributes to the photocatalytic activity of HC due to the following reasons [24]: (1) the effective separation of the photogenerated electrons and holes; and (2) the mitigation of the recombination of the electron/hole pairs. The valence-band holes (h 1 ) are powerful oxidants, which can be created holes draw electrons from the hydroxyl groups and produce hydroxyl radicals (•OH) while the conductionband electrons (e 2 ) are good reductants, which can be transferred to the O 2 in solution to yield activated oxygen species or to the adsorbed H 1 to form H 2 .…”
Section: Discussion Of the Photocatalytic Mechanismmentioning
confidence: 99%